The effect of work engagement and work experience on job performance freelance at event organizer famouz studio - Fadia Annisa; Suhairi Suhairi; Tri Inda Fadhila Rahma (LPMP Imperium, 2026)
This study aims to explore the impact of work engagement and professional experience on the performance of freelancers at the Famouz Studio Event Organizer in Medan. Famouz Studio employs freelancers to handle various events. However, it was found that the level of engagement and experience of each freelancer varies. This research was conducted using a quantitative approach and a survey method with 70 freelancers. Analysis conducted using multiple linear regression revealed that both work engagement and professional experience have a positive and significant impact on job performance, both individually and together. This means that the higher the enthusiasm, dedication, and work experience of freelancers, the better their work results. This study highlights the crucial role of human resource management, especially for contract workers, in improving the overall performance of an organization. Public Interest Statement: This research is significant for freelancers and organizations like Famouz Studio. Understanding how work engagement and experience affect performance provides insights to improve productivity and service quality. The findings benefit both the event organizer industry and freelancers’ professionalism, welfare, and career development in this sector.